Analysis of the profile of sustainable procurements conducted by military organizations of the brazilian army - Pereira, Alexandre de Oliveira; Senna, Ana Júlia Teixeira; Alves, Ricardo Ribeiro; Gracioli, Cibele Rosa (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2014)
Responsibility for environment preservation is now a major determining theme of government and non-government actions. Nowadays, the government has started inserting the environmental question in its public policies, especially, in the acquisition of products and in hiring services. By virtue of the importance of the environmental dimension in contemporary society and the relevance of the theme over purchases and sustainable procurements, the objective of this paper consisted in analyzing the sustainable procurements conducted by military organizations of the Brazilian Army and verify the environmental criteria used in the public purchases by these institutions. To this end, this paper is structured in the following way; primarily, a bibliographic revision was conducted on public bids, government purchases and sustainable procurements. Later on, secondary data were collected from government sources. Analyses included procurements conducted by military organizations of the Brazilian Army containing environmental criteria available at site “Comprasnet”, purchasing portal of the federal government, with the aim to diagnose the characteristics of sustainable procurements carried out by the institutions. Analyzed data attested to the fact that sustainable procurements were barely represented in the acquisitions performed by the Army. Furthermore, it was ascertained that there was little variety of bid items. The most demanded environmental characteristic at the biddings was related to items made from recycled raw material. It was observed that the environmental requirements demanded at the bidding contests were not much exacting, signaling that public sustainable purchases should be implemented gradually in our national economy.